2023
DOI: 10.1200/jco.2023.41.4_suppl.100
|View full text |Cite
|
Sign up to set email alerts
|

Phase III FIRE-4 study (AIO KRK-0114): Evaluation of first-line treatment efficacy of FOLFIRI/cetuximab in patients with RAS-WT mCRC receiving the first cycle of treatment with chemotherapy only.

Abstract: 100 Background: FIRE-4 (AIO KRK-0114) is performed in RAS wild-type (wt) mCRC patients. This randomized study tests the efficacy of early switch maintenance during 1st-line therapy (part 1) and re-challenge with cetuximab (part 2) in later-line treatment. In part 1, all patients received first-line induction treatment with FOLFIRI plus cetuximab (FOLFIRI/Cet). In arm A, patients were randomized to continue FOLFIRI/Cet until progression or intolerable toxicity. In arm B, patients received FOLFIRI/Cet for 8-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent phase III trial (FIRE‐4) reported that an early switch after 8–12 cycles from FOLFIRI plus cetuximab to maintenance therapy with 5‐fluorouracil/capecitabine plus bevacizumab was not associated with superior efficacy compared to the continued cetuximab administration 16 . However, no detrimental effects were reported in patients who switched to bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase III trial (FIRE‐4) reported that an early switch after 8–12 cycles from FOLFIRI plus cetuximab to maintenance therapy with 5‐fluorouracil/capecitabine plus bevacizumab was not associated with superior efficacy compared to the continued cetuximab administration 16 . However, no detrimental effects were reported in patients who switched to bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase III trial (FIRE‐4) reported that an early switch after 8–12 cycles from FOLFIRI plus cetuximab to maintenance therapy with 5‐fluorouracil/capecitabine plus bevacizumab was not associated with superior efficacy compared to the continued cetuximab administration. 16 However, no detrimental effects were reported in patients who switched to bevacizumab. The treatment approach evaluated in FIRE‐4 was different from that in the present trial in several aspects, including the timing of the switch and the strength of backbone chemotherapy after the switch to bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
“…Numerically longer anti-EGFR-free intervals and time from the last anti-EGFR administration to firstline disease progression were observed in the group with RAS/ BRAFV600E wt ctDNA. Translational data from the randomized FIRE4 trial showed a significant correlation between the duration of the exposure to first-line anti-EGFRs and the occurrence of RAS mutations, though in the absence of any overall survival (OS) difference between the groups of patients acquiring or not RAS mutations in ctDNA (23).…”
mentioning
confidence: 99%